Sodium Fluorescein for Spinal Intradural Tumors - Olguner, Semih Kivanc; Arslan, Ali; Açık, Vedat; İstemen, İsmail and Can, Mehmet and Gezercan, Yurdal and Ökten, Ali İhsan (Frontiers in Oncology, 2021)
Technological innovations in spinal intradural tumor surgery simplify treatment. Surgical treatment of cranial benign and malignant pathologies under a microscope with sodium (Na)-fluorescein guidance has often been reported, but few studies have focused on spinal intradural tumors. We aimed to investigate the usefulness of Na-fluorescein under yellow filter in intradural spinal tumor surgery by retrospectively reviewing cases involving intramedullary and extramedullary tumors operated under the guidance of Na-fluorescein. Forty-nine adult patients with a diagnosis of spinal intradural tumor operated under a yellow filter (560 nm) microscope using Na-fluorescein dye were included in the study. Demographic data, such as age and sex, neurological status, the extent of tumor resection, histopathological diagnosis, Na-fluorescein staining pattern, and its usefulness during surgery were noted and statistically analyzed. Of all recruited patients, 26 women (53.1%) and 23 men (46.9%), were included for analysis. The age range of the patients was 18-64 years, with a mean age of 41.6 ± 13.9. An intradural intramedullary mass was found in 30.6% (n = 15) of the patients, and an intradural extramedullary mass in 69.4% (n: 34). While Na-fluorescein staining was homogeneous in all intradural extramedullary tumors, 73.3% (n: 11) of intradural intramedullary tumors were homogeneous, and 13.3% (n: 2) moderately heterogeneous. In the whole study group, the Na-fluorescein staining pattern was helpful in surgical resection in 47 cases (95.9%). While 34/34 (100%) found it helpful for extramedullary tumors, 13/15 (86.7%) did in intramedullary tumors, and for 2/15 (13.3%) it was not. In conclusion, Na-fluorescein helps in distinguishing tumor from healthy tissue in intradural extramedullary and intramedullary tumor surgery under a yellow filter microscope in most cases, thus providing convenient assistance to surgeons.